PROSEDUR PENANGKAPAN TERHADAP PELAKU TINDAK PIDANA NARKOTIKA YANG MELARIKAN DIRI KELUAR NEGERI MENURUT HUKUM PIDANA INTERNASIONAL - Bangonang, Deyti Daniyarti (LEX CRIMEN, 2013)
Arrest Procedures,Â  in this present case: Narcotics offenses among people shows evidence of an increasing trend. Lack of full support in the government to combat the international narcotics network correlates with international cooperation on the issue. With law enforcement efforts to prevent and combat both criminal narcotics and criminal attempts to restore major narcotics players who have fled abroad, in addition to involving all components of society, it is expected that the Indonesian government may also increase international cooperation on the issue on a bilateral, regional and multilateral scale, as well as technical cooperation in accordance with the provisions of current legislation. Keywords: Arrest , Procedures, Narcotics, Criminals, Increase, Government.